2018
DOI: 10.1155/2018/2413874
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Pork Adulterated in the Beef and Mutton by Infrared Spectroscopy

Abstract: Consumers concern about food adulteration. Pork meat is the principal adulterated species of beef and mutton. The conventional detection methods have their own limitations; therefore, we sought to develop an efficient and economical identification method using an infrared spectroscopy technique for meat. The Mahalanobis distance method was used to remove outliers in spectrum data. Interferences were eliminated using multiple scatter correction, standard normal variate, Savitzky-Golay smoothing, and normalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…However, pork adulteration in beef has been discovered in the market [3], [6]. The practice of mixing beef with pork is sometimes done for economic reasons [7], [8]; the seller adulterates pork in beef because pork is cheaper than beef [9]. Recent research has discussed meat authentication using visual detection.…”
Section: Introductionmentioning
confidence: 99%
“…However, pork adulteration in beef has been discovered in the market [3], [6]. The practice of mixing beef with pork is sometimes done for economic reasons [7], [8]; the seller adulterates pork in beef because pork is cheaper than beef [9]. Recent research has discussed meat authentication using visual detection.…”
Section: Introductionmentioning
confidence: 99%
“…While using SVM, the classification models were worse than using PLS-DA with R 2 calibration, R 2 prediction, RMSEC, RMSECV, and RMSEP were of 0.97, 0.96, 0.15, 0.17, and 0.24, respectively. Therefore, it can be concluded that FTIR spectroscopy coupled with PLS-DA provided better classification method than SVM method, which can be used as effective tools to identify beef, mutton and that adulterated with pork [46].…”
Section: Methodsmentioning
confidence: 99%
“…Authentication in meats is required for foods that are labeled as individual meats [71]. Horsemeat in minced beef [72], beef and mutton in pork [73], and rainbow trout in Atlantic salmon [74] each require sufficient data specific to substances to be labeled to assure the meat contaminant is properly characterized in order to identify markers characteristic of each additional component. Spectral data on the primary meat preferentially needs to be oversampled relative to that of a contaminant, or of minor or occasional components that could be misinterpreted as unrelated to the original meat.…”
Section: Vibrational Spectroscopymentioning
confidence: 99%